2010
DOI: 10.1007/s00227-010-1499-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential utilization of biochemical components during larval development of the spider crab Maja brachydactyla (Decapoda: Majidae)

Abstract: Changes in lipid class, fatty acid, fat-soluble 10 vitamins, amino acid and minerals were studied during 11 larval development of Maja brachydactyla Balss, 1922 in 12 order to provide information of its ontogeny and evaluate 13 possible dietary deficiencies and constraints. Four dif-14 ferent batches were analyzed from hatching to meta-15 morphosis using enriched Artemia as food. Cultured 16 larvae were in a good nutritional condition as confirmed 17 by the continuous lipid accumulation throughout ontog-18 eny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Previous studies on the same species (Anger and Harms 1990) reported a maximum dry weight of about 160 mg for the ZI instar, 224 mg for ZII, and 275 mg for megalopa, whereas Andrés et al (2008) found a maximum of 389 mg in megalopa. In the present study, newly hatched ZI were heavier than in the two previous studies, and megalopa even reached 479 mg in stage D 2 (i.e.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies on the same species (Anger and Harms 1990) reported a maximum dry weight of about 160 mg for the ZI instar, 224 mg for ZII, and 275 mg for megalopa, whereas Andrés et al (2008) found a maximum of 389 mg in megalopa. In the present study, newly hatched ZI were heavier than in the two previous studies, and megalopa even reached 479 mg in stage D 2 (i.e.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, differences observed between studies might also, at least in part, be due to geographic variations among conspecific populations (cf. Andrés et al 2008, and present study: northwestern Spain; Anger and Harms 1990: French coast of the channel region).…”
Section: Discussionmentioning
confidence: 87%
“…The species possesses some interesting biological features, such as high growth rate and plasticity, and great adaptability to reproduction in captivity, showing high fecundity and successive egg clutches during the breeding season, allowing seeds production during the whole year (González-Gurriarán, Fernández, Freire & Muiñ o 1998). Until now, the culture of this species is based on the production of seeds from wild mature animals that are just kept for one season for spawning purposes (González-Gurriarán et al 1998;Andrés, Estévez, Hontoria & Rotllant 2010), which might compromise the conservation of this overexploited species (Freire, Bernárdez, Corgos, Fernández, González-Gurriarán, Sampedro & Verísimo 2002). Until now, the culture of this species is based on the production of seeds from wild mature animals that are just kept for one season for spawning purposes (González-Gurriarán et al 1998;Andrés, Estévez, Hontoria & Rotllant 2010), which might compromise the conservation of this overexploited species (Freire, Bernárdez, Corgos, Fernández, González-Gurriarán, Sampedro & Verísimo 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, research on this species has been focused on larval and juvenile development (Andrés, Estévez & Rotllant 2007;Andrés, Estévez, Anger & Rotllant 2008;Guerao & Rotllant 2009) and reproduction (Rotllant, González-Gurriarán, Fernández, Benhalima & Ribes 2007;Simeó, Ribes & Rotllant 2009;. Until now, the culture of this species is based on the production of seeds from wild mature animals that are just kept for one season for spawning purposes (González-Gurriarán et al 1998;Andrés, Estévez, Hontoria & Rotllant 2010), which might compromise the conservation of this overexploited species (Freire, Bernárdez, Corgos, Fernández, González-Gurriarán, Sampedro & Verísimo 2002). Hence, its sustainable culture requires long-term maintenance of broodstock to be independent from wild caught animals.…”
Section: Introductionmentioning
confidence: 99%
“…The larval development of this species comprises two zoeal stages and a megalopa, which were morphologically studied by Lebour (1927Lebour ( , 1928, Paula (1985), Clark (1986), Ingle (1992) and Guerao et al (2008). Under constant experimental conditions of salinity (36 ‰) and temperature (18ºC), metamorphosis to the first juvenile crab instar is reached about 18 days after hatching (Andrés et al, 2007(Andrés et al, , 2008Guerao et al, 2008;Palma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%